Modeling Entrepreneurship Intentions: An Essay of Typology - Branchet, Bénédicte; Boissin, Jean-Pierre; Hikkerova, Lubica (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
From the standpoint of a psycho-sociological intention model adapted from the Theory of Planned Behavior, we analyze factors modeling students’ entrepreneurship intentions, as expressed by 7000 students of 24 different nationalities. We highlight the existence of differences in certain beliefs between countries. We then propose three structuring factors of student entrepreneurship intentions: type of entrepreneurship vision, opinion, and perceived capacity to create a business. Next, we construct a typology of student behaviors toward entrepreneurship intentions manifesting in six characterized clusters. We find that entrepreneurship intention behaviors are relatively supranational and are only slightly influenced by national education systems.